(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
The article analyses unfavorable factors arising during dismantling and moving of crane structures, mechanical equipment in the conditions the urban transport network, access roads to the long-term storage warehouse. Paper is based on the analysis the causes accidents and emergencies and shows that many them are man-made (technical condition of buildings, structures, equipment and engineering networks, poor organization work technology).Article presents developments in the analysis process of dismantling a tower crane in the conditions limited space a construction site, urban development. Purpose of the research - identify factors affecting the safety dismantling process, analyses and systematize data e progress work in a cramped construction site and identify options dismantling cranes that are most beneficial enterprise. Proposed methodology is aimed at reducing the risks of the technological process dismantling crane structures, which is an urgent task in the field construction. Assessing principles the conditions limited space a construction site during construction depending on the technology work production are presented. Recommendations for dismantling metal structures tower-type cranes and determining technological safety are given. Methodology allows identifying and assessing risks when planning the decommissioning procedure for a tower crane. In this case, it is possible to optimize material costs economically to reduce the overall cost of construction. The efficiency of this method is increased when decommissioning several cranes involved in construction. Study of the state structures, considering the most unfavorable combination influences, was considered in accordance with the methodological approach to substantiate composition and structure parameters of structural durability for managing technological safety by reducing risks. The possibility ensuring service life structures through the combined use of analysis methods has been established, which is due to the rational design, development and use advanced means planning and ensuring the technology of construction processes.